Rapid response petrology for the opening eruptive phase of the 2021 Cumbre Vieja eruption, La Palma, Canary Islands - Pankhurst, Matthew J.; Scarrow, Jane H.; Barbee, Olivia A.; Hickey, James; Coldwell, Beverley C.; Rollinson, Gavyn K.; Rodríguez-Losada, José A.; Martín Lorenzo, Alba; Rodríguez, Fátima; Hernández, William; Calvo Fernández, David; Hernández, Pedro A.; et al. (Volcanica, 2022)
How and why magmatic systems reactivate and evolve is a critical question for monitoring and hazard mitigation efforts during initial response and ongoing volcanic crisis management. Here we report the first integrated petrological results and interpretation provided to monitoring authorities during the ongoing eruption of Cumbre Vieja, La Palma, Canary Islands, Spain. The first eruptive products comprised simultaneous Strombolian fountain-fed lava flows and tephra fall from near-continuous eruption plumes. From combined field, petrographic and geochemical analyses conducted in the 10 days following sample collection, we infer low percentage mantle melts with a variably equilibrated multimineralic crystal-cargo and compositional fractionation by winnowing during eruptive processes. Hence ‘rapid response’ petrology can untangle complex magmatic and volcanic processes for this eruption, which combined with further study and methodological improvement can increasingly assist in active decision making.